Предмет: Математика,
автор: 11YaNa11
Решите уравнение:
а) 2x-4-3(x-4)=-2(-3-х)-4
б) -1-10х=-9х+1
в) ( / - дробь ) х - х/12 = 55/12
г) 3х+5+(х+5)=(1-х)+4
Ответы
Автор ответа:
0
a)2x-4-3(x-4)=-2(-3-x)-4
2x-4-3x-12=6+2x-4
2x-3x-2x=6-4+4+12
-3x=18
x=-6
2x-4-3x-12=6+2x-4
2x-3x-2x=6-4+4+12
-3x=18
x=-6
Похожие вопросы
Предмет: Математика,
автор: dzharasov03
Предмет: Алгебра,
автор: davyddamzin917
Предмет: Английский язык,
автор: denistv96
Предмет: Алгебра,
автор: tomiris2002
Предмет: Обществознание,
автор: evakirina13